Penerapan Model Pembelajaran Discovery Learning Berbasis Lesson Study Dalam Upaya Peningkatan Kemampuan Komunikasi Matematik Siswa Kelas X Mipa-3 Sma Negeri 5 Kendari - Kodirun .; Busnawir .; Elvita Beliana Viktor (Jurnal Pendidikan Matematika, 2016)
This research is motivated by the lack of mathematical communication in students. The research was conducted of class X MIPA-3 at SMAN 5 Kendari in academic term 2015/2016. The instrument used the mathematical communication ability test and observation sheets for teachers and students to condition the implementation stage. The procedure of this study consists of: (1) the planning stages (plan), (2) the phase of the (do), and (3) stages of reflection (check). Based on the results of data analysis and discussion we concluded that the average math student communication skills in the final test showed 78.2 score for both criteria. An average increase from initial tests to the final test resulted 17.89 which is 69.23% of students who have met the criteria of this research. The average indicator of mathematical communication capabilities following the first indicator increased by 0.37, an increase of 0.61 for second Indicators, third  indicator increased by 0.65 and Four indicator for 1.23. Based on the results showed that the communication skills of students in mathematical statistics materials have increased based on test results at the end of a given material.